Subcellular localization of benzodiazepine/GABAA receptors in the cerebellum of rat, cat, and monkey using monoclonal antibodies - Somogyi, P (J Neurosci, 1989)
Two monoclonal antibodies, bd-17 and bd-24, specific for the beta- and alpha-subunit of the GABAA/benzodiazepine receptor/chloride channel complex, respectively, were used to determine the subcellular distribution of immunoreactivity in the cerebellum by electron microscopy. The 2 antibodies showed similar antigen distribution on the plasma membrane (except in the rat; bd-24 does not recognize the rat antigen), but intracellular immunoreactivity was more prevalent for the alpha-subunit. The plasma membrane of all neuronal types was immunopositive. The degree of immunoreactivity varied greatly between different types of cell, but it was stereotyped among individual cells of the same type. Granule cells showed the strongest immunoreactivity, not only on their dendrites which receive synapses from GABA-containing Golgi cell terminals, but also on their somata which do not receive synapses. Stellate and basket cells were somewhat weaker in immunoreactivity. Purkinje cells were only weakly positive on their somatic membrane but stronger on their dendritic shafts and spines. Golgi cells showed negligible if any immunoreactivity. Neurons of the deep cerebellar nuclei were strongly immunopositive along their plasma membrane. Immunoreactivity was strong in cisternae of the endoplasmic reticulum and in the Golgi saccules of stellate and basket cells, variable in Purkinje cells, while granule cells were rarely immunoreactive intracellularly. It is suggested that these differences reflect differences in the turnover of the receptor complex in the different cell types. The synaptic clefts established by boutons of the GABAergic stellate, basket, and Golgi cells were immunopositive, as were many synapses in the deep cerebellar nuclei. However, immunoreactivity was also present along the nonjunctional plasma membrane, and it was concluded that this reflected the distribution of the antigen. The synaptic clefts at the presumed glutamate-releasing parallel and mossy fiber terminals were almost always immunonegative. No immunoreactivity was detected on axons, nerve terminals, or glial cells. The results demonstrate that different neuronal types express the GABAA/benzodiazepine receptor/chloride channel complex to different degrees. The distribution of the receptor complex suggests that the cellular topography of GABAergic influence is not governed by the precise spatial arrangement of the receptors but by the precise placement of the GABA-releasing terminals, a characteristic of the cerebellar circuit.